Combined pulsed dye laser and fiberoptic Nd-YAG laser for the treatment of hypertrophic port wine stain. (18th August 2017) - Radmanesh, Mohammed; Radmanesh, Ramin
ABSTRACT: The hypertrophic Port Wine Stain (PWS) is only partially and superficially treated with the Pulsed dye laser (PDL) because of its limited depth of penetration. We used combined PDL and fiberoptic 1444-nm Nd-YAG laser to treat a case with hypertrophic PWS.Method : After tumescent anesthesia, few holes were made by a 16-gauge needle on different sides of the lesion. The fiberoptic tip of 1444-nm Nd-YAG laser was inserted within the holes and was pushed forward while triggering. In a fan pattern and by a back and forth movement, the subcutaneous and deep dermal areas were coagulated. The skin and outer mucosal surfaces were then treated by PDL. The fiberoptic system used was Accusculpt 1444-nm Nd-YAG laser (Lutronic lasers, South Korea), and the PDL used was 585 nm Nlite system (Chromogenex UK). The parameters used for PDL were fluence = 9 Joules/cm 2 and the spot size was 5 mm. The parameters used for fiberoptic 1444-nm Nd-YAG laser were: Pulse rate = 30 Hz, pulse energy = 300 mJ, power = 6 W, and the total energy = 4000 J for the whole face and mucosa.Result : Little sign of regression and moderate purpura were detected immediately after combined fiberoptic Nd-YAG and PDL therapy. The lesion gradually regressed within 4 months with satisfactory color and volume change.Conclusion : Combined fiberoptic Nd-YAG laser and PDL can be used for the treatment of deeper and superficial layers of hypertrophic PWS.